Waqf Disputes and Procedural Justice Through Proof of PledgesThe Status of Nazhir in Religious Courts - Faisal Faisal (Jurnal Hukum Replik, 2026)
This study examines the resolution of waqf disputes in Religious Courts, focusing on proving the waqf pledge, the legal standing of the nazhir, and the application of procedural justice. Waqf disputes often arise due to disorderly waqf administration, weak evidence of the pledge, unclear status of the waqf object, or conflicting interests between the heirs, the nazhir, and the community. This study uses a normative juridical method with a statutory, conceptual, and case-based approach. The results of the discussion indicate that proving the waqf pledge plays a crucial role in determining the legal status of the waqf object. The Waqf Pledge Deed, waqf land certificate, witness testimony, and the use of the waqf object in the community can form the basis for the judge's considerations. Furthermore, the nazhir holds a crucial position as the party responsible for safeguarding and maintaining waqf assets, but their legal standing must still be legally tested. Procedural justice is necessary to ensure that all parties have an equal opportunity to present their arguments and evidence. This research confirms that procedural law in waqf disputes must provide legal certainty, justice, and benefits for the protection of waqf assets.Keywords: waqf disputes, waqf pledge, nazhir, procedural justice, Religious Courts.